The WW‐FINGERS‐SARS‐CoV‐2 initiative: a multinational survey to assess the effects of the COVID‐19 Pandemic on Lifestyle and Psychosocial factors relevant to Brain Health. (20th December 2022) - Mangialasche, Francesca; Rocha, Ana Sabsil Lopez; Lehtisalo, Jenni; Solomon, Alina; Middleton, Lefkos T; Thunborg, Charlotta; Levak, Nicholas; de Jager, Celeste A; Price, Geraint J; Rydström, Anders; Ngandu, Tiia; Kivipelto, Miia; et al.
Abstract: Background: global population aging and forecasted trends of modifiable risk factors for dementia and Alzheimer's disease (AD) make prevention of these conditions an urgent priority. The World‐Wide FINGERS (WW‐FINGERS) global network of multidomain trials for dementia risk reduction and prevention is at the forefront of efforts to find effective and sustainable solutions for diverse population. The COVID‐19 pandemic has caused changes in the mental and physical health of older adults, which can influence dementia risk and prevention opportunities. Methods: The WW‐FINGERS‐SARS‐CoV‐2 survey was developed to assess direct and indirect effects of the COVID‐19 pandemic in older adults. The questionnaire measures changes in lifestyle factors (e.g., diet, physical activity), management of chronic noncommunicable diseases (e.g., diabetes, hypertension), and psychosocial factors ‐including depressive symptoms, sleep disorders, social isolation‐ that are relevant to cognition. Both a pen‐and‐paper and a digital version of the survey have been developed in several languages. The digital version is supported through REDCap (Research Electronic Data Capture), which is used also for harmonized data collection. Results: 30 countries are participating in the survey. As for January 2022, data have been collected from 20 countries, with 23000+ participants. Local adaptations and piloting were done to optimize implementation in clinical‐based and population‐based settings. Participants are in the at‐risk spectrum for dementia: from normal cognition to pre‐dementia cognitive symptoms. Timing of the survey implementation varies across populations, allowing to capture short, medium and long‐term effects of the pandemic and restrictions measures. Some countries have used the survey to recruit participants in multimodal prevention trials. An updated report of the survey status and main results will be presented. Conclusion: The WW‐FINGERS‐SARS‐CoV2 survey is a joint global action of the WW‐FINGERS network which can inform better care of older adults in the context of a pandemic. The survey is also a valuable tool for pre‐screening of participants for prevention trials, and results can inform adaptions to ensure successful recruitment and adherence in forthcoming multidomain trials for dementia prevention in older adults.